The Impact of Damage on the Annulment of Non-Binding Contracts: A Comparative Fiqh Study - Al- Harbi, Abdul Aziz Nasser; Mansour, Mohammed Khaled (Dirasat: Shari’a and Law Sciences, 2023)
Objectives: This study aimed to identify the impact of damage on the annulment of non-binding contracts via knowing the nature of these contracts and their characteristics. It also aimed to identify the penalty of annulling non-binding contracts. Methods: This study used the inductive approach to navigate through the Fiqh books to unearth the aspects related to non-binding contracts. It also used the the analytical approach to analyze the scientific material as well as the comparative approach to peruse what Fiqh intellectuals contend and come to a final word about the topic in question. Then the study resorted to the deductive approach to contemplate the damage-induced annulment of non-binding contracts. Results: The researchers in this study concluded that the two parties included in non-binding contracts are fully independent and free to annul the contract anytime. They also concluded that non-binding contracts have conditions which differ from one contract to another for them to be annulled. Conclusions: The study shows that there is an evident impact of damage on non-binding contracts. It also recommends conducting further research pertinent to the impact of damage on the annulment of contracts, especially in contemporary contracts and their applications to contemporary financial transactions.